Pemanfaatan Media Online Bagi Kelompok Gerai PKK Nagari Parit Malintang Kecamatan Enam Lingkung Kabupaten Padang Pariaman - Adree Octova; Yoszi Mingsi Anaperta; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. Nagari Parit Malintang is one of the Nagari located in the district of Enam Lingkung Padang Pariaman. The daily activities of the community are rough, farming and farming. Besides that, there were also efforts made from the small business sector and the household handicraft industry. One of the business groups is the Nagari PKK Outlet group. This business group has results in the fields of pearls and coconut, coconut and derivatives, as well as cooking. In the course of this business group from there. The low public interest will have a positive impact in the future. In this community service activity, online introduction media will be conducted in an effort to increase sales in this Nagari. The method used is technology, assistance and calculation in the production process (packaging). The activity began with a library, conducting an initial survey to the location of activities related to online media in businesses and businesses, introducing various online promotional media, mentoring in creating accounts and online content and ending with production packaging expenditures in order to have a match selling market needs when this. The results of community service activities that allow groups to have online sales accounts from various online services and applications, enable a more strategic market and can increase sales results..Keywords: Online Media, Information Technology, Marketing Strategies